Pants ahoy - Snow, Alan. (Oxford : Oxford University Press, 2008)
When Arthur is cornered by the frightful Snatcher and his men, there seems to be no way out. But luckily help is at hand in the form of a retired judge, a timid cabbagehead, and some very excitable boxtrolls.It's monsters to the rescue!This is the first part of the incredible Here Be Monsters saga - now published in paperback in three easy-to-digest volumes. Illustrated throughout with nearly two hundred incredible black and white drawings, this is the start of an astonishing journey into the unbelievably weird world of Ratbridge.
7.4
5-8.
5-8
Keywords: Magic -- Juvenile fiction; Trolls -- Juvenile fiction; Fantasy; Magic -- Fiction; Trolls -- Fiction; Magic -- Fiction; Trolls -- Fiction; Ratbridge (Imaginary place) -- Fiction; Fantastic fiction